Reasonable selection of a topical therapy for different forms of acne - M. M. Kokhan; YU. V. Keniksfest; A. I. Polishchuk (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Modern data of the acne pathogenesis, including the role of Propionibacterium acnes in the early stages of the acne formation and their provocative role in the development of the inflammatory process are presented. Priority importance of topical retinoids and combination products containing fixed combinations adapalene with benzoyl peroxide or antibiotic clindamycin in the acne treatment are shown. There are presented the facts of the effectiveness of Clenzit gel (adapalene 0.1%) and Clenzit-C (adapalene 0.1% and clindamycin phosphate 1.0%) and an algorithm for the choice of drug depending on clinical and morphological features of the skin process that allows to optimize the treatment of patients with various forms of acne.